2008
DOI: 10.1002/14651858.mr000002.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Technical editing of research reports in biomedical journals

Abstract: Surprisingly few studies have evaluated the effects of technical editing rigorously. However there is some evidence that the 'package' of technical editing used by biomedical journals does improve papers. A substantial number of references in biomedical articles are cited or quoted inaccurately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 92 publications
0
47
1
Order By: Relevance
“…24.2%, falls within the range reported for medical and health science disciplines (Table 2) although the various studies used an array of methods and categories. A summary of the research on citation malpractice in medicine calculated that, from a total of 3836 citations checked, a median of 20% were 'inaccurate' (Wager & Middleton 2008). Our counts, however, are likely to be underestimates as we only examined single citations and predict more errors will occur when assertions are supported by a string of references.…”
Section: Discussionmentioning
confidence: 90%
“…24.2%, falls within the range reported for medical and health science disciplines (Table 2) although the various studies used an array of methods and categories. A summary of the research on citation malpractice in medicine calculated that, from a total of 3836 citations checked, a median of 20% were 'inaccurate' (Wager & Middleton 2008). Our counts, however, are likely to be underestimates as we only examined single citations and predict more errors will occur when assertions are supported by a string of references.…”
Section: Discussionmentioning
confidence: 90%
“…-31 16 13 1 -2 -ERJ 67,340 100 12 7 3 22 6 11 -2 1 -T 38,905 100 14 7 3 24 12 6 -1 2 -R 17,705 100 17 7 2 26 16 7 --1 2 sultants in the editorial offices [2,4,9] , limitations of the number of references [2,4,9,10] , or adopting a uniform system of citation for all journals in a given field, thereby creating a standard by which citations could be compared electronically against a scrupulously accurate database [2,9] . Additionally, technical editing may therefore improve the accuracy of citations [2,6] . All of these suggestions have the potential to further decrease the frequency of errors.…”
mentioning
confidence: 99%
“…Trials on open peer review have shown mixed results on the impact on quality of review, with one study demonstrating improved quality (19). In some studies, it has been shown that intensive editorial review may correlate to fewer errors in abstracts and references, whereas providing author's instructions may correlate to fewer errors in references and improved reporting of ethics requirements (20). Methodological review of research articles may be expected to improve the quality of published articles.…”
Section: Discussionmentioning
confidence: 99%